Estrategias de promoción digital desde una perspectiva intercultural para Radio Novedades. - Erazo Falcón, Oscar Andrés (2023)
This research focuses on obtaining the necessary information for the implementation of a radio program as a digital strategy, with which to highlight the customs and traditions of the different peoples and nationalities of Ecuador, especially Latacunga city; The program has been implemented on Novedades 1100 AM radio and on different digital platforms. The name of the designed program is “Mashkeando Cultura" which tells the story, cultural identity and environment of Latacunga in an alternative way. Bibliographical-documentary research was applied to obtain the theoretical part in the radio content proposal, supporting the work under a qualitative approach, through observation as a research technique, complementing it with in-depth interviews. The research itself focused on identifying radio communication products focused on intercultural issues, in order to identify the competition, new trends on the application of digital strategies; This research has allowed the development of a pilot program that has already been implemented on Radio Novedades 1100 AM.